An Issue of Formation and Development of Transport and Logistics Infrastructure in The Russian Federation - Nadezhda BULATOVA; Dmitriy RODIONOV; Alexey BATAEV; Alexey ALEXEEV; Darya KRYZHKO (Communications of International Proceedings, 2020)
The paper considers the problem of forming the network of transport and logistics centers in the territory of the Russian Federation as the foundation for transport and logistics infrastructure. Special attention is paid to the legal and regulatory framework of building this system. The authors analyze characteristics of transport and logistics centers, list the network of the existing centers located on key haulage routes. The experience of building such centers helped work out a strategy of development of transport and logistics infrastructure in the Russian Federation, which is aimed at building up other centers in all federal areas. It is noted that their location is in line with the system solutions of the “Concept of creation of terminal and logistics centers on the territory of the Russian Federation” developed by JSC RZD (“Russian railways”).  Following the above-mentioned strategy, most of these centers will serve the transport and logistics systems of trade and freight movements in the international “North-South”, “East-West” transport corridors, including the China-Mongolia-Naushki-Trans-Siberian trunk line. Consequently, the paper considers problems and development prospects of the transport and logistics infrastructure in the Republic of Buryatia. The authors highlight that currently the cooperation prospects between the three states in creating the integrated transport and logistics infrastructure within the program of the “Russia-Mongolia-China” economic corridor are related to formation and development of the ecosystem of the single Eurasian digital transport and logistics platform.
Keywords: Transport and Logistics System; Transport Infrastructure; Economic Corridor; Ecosystem